Southern Parties and Elections : Studies in Regional Political Change - Baker, Tod A.; Moreland, Laurence W.; Steed, Robert P. (Book collections on Project MUSE., 1997)
This fresh look at southern politics clarifies the recent and dramatic development of party competition in the South. Southern politics has changed dramatically during the past half century. While new developments have touched virtually every aspect of the region's politics, change has been especially marked in the South's political party and electoral systems. Southern Parties and Elections explores the contemporary developments in party realignment and examines the relationship between regional party change and electoral behavior and the larger patterns in national politics. The collection'